A novel, essential trans-splicing protein connects the nematode SL1 snRNP to the CBC-ARS2 complex. Issue 13 (23rd June 2022) - Fasimoye, Rotimi Yemi; Spencer, Rosie Elizabeth Barker; Soto-Martin, Eva; Eijlers, Peter; Elmassoudi, Haitem; Brivio, Sarah; Mangana, Carolina; Sabele, Viktorija; Rechtorikova, Radoslava; Wenzel, Marius; Connolly, Bernadette; Pettitt, Jonathan; et al.
Abstract: Spliced leader trans -splicing is essential for gene expression in many eukaryotes. To elucidate the molecular mechanism of this process, we characterise the molecules associated with the Caenorhabditis elegans major spliced leader snRNP (SL1 snRNP), which donates the spliced leader that replaces the 5′ untranslated region of most pre-mRNAs. Using a GFP-tagged version of the SL1 snRNP protein SNA-1 created by CRISPR-mediated genome engineering, we immunoprecipitate and identify RNAs and protein components by RIP-Seq and mass spectrometry. This reveals the composition of the SL1 snRNP and identifies associations with spliceosome components PRP-8 and PRP-19. Significantly, we identify a novel, nematode-specific protein required for SL1 trans -splicing, which we designate SNA-3. SNA-3 is an essential, nuclear protein with three NADAR domains whose function is unknown. Mutation of key residues in NADAR domains inactivates the protein, indicating that domain function is required for activity. SNA-3 interacts with the CBC-ARS2 complex and other factors involved in RNA metabolism, including SUT-1 protein, through RNA or protein-mediated contacts revealed by yeast two-hybrid assays, localisation studies and immunoprecipitations. Our data are compatible with a role for SNA-3 in coordinating trans -splicing with target pre-mRNA transcription or in the processing of the Y-branch product of the trans -splicing reaction.